The Contributions in Education through Literature (A Narrative Inquiry Study of Prof. Toni Morrison in The United States of America) - Andina Ichsani; Zainal Rafli; Nuruddin Nuruddin (Loquen, 2018)
Abstract: Biography consists of life’s story in a unique record form, a narrative impulse, establishes the importance of stories, and provides an open illustrative example of the analysis of an adult learner's story. This paper provides a step-by-step account of how a researcher conducted a narrative research study analysis and developed an organizational structure useful for other qualitative researchers. Prof.Toni Morrison as purposeful sampling is widely recognized as a first lady of literature in American’s prominent novelist, who magnificently explores the minority life of the black people identity to the surface in The United States of America, especially that of black women story. Her Nobel Prize Lecture, in which she consistence tells a story of a black woman, history of slavery, racism, post colonialism, and education rights for all. Her life story and contributions in education through literature space can be regarded as a shaper of Prof. Morrison’s today and the look of education equality. In her 85th she is still teaching, being mother, and continue writing as her passions. Several interviews dialogue between the journalists through her novels and the young people is full of inspirational stories, wisdom and profoundness. Her life story is indeed worth to learn as a study material especially in English Language and Literature proficiency.